Revitalisasi Metode Ceramah dalam Pembelajaran PAI: Menjawab Tantangan Gaya Belajar Generasi Alpha - Khuzaini, Iqfal; Supratama, Riky (Indo Publishing, 2025)
This study aims to analyze and revitalize instructional methods in Islamic Religious Education (PAI) to align with the learning needs and characteristics of Generation Alpha. Using a library research approach, this study examines recent scholarly articles on pedagogical innovation, digital learning, and the effectiveness of the lecture method in contemporary educational contexts. The findings indicate that digital-native learners prefer visual, interactive, and collaborative learning experiences, which necessitates updating traditional methods such as lectures without diminishing their historical and pedagogical value. The analysis reveals that the scientific approach, constructivism, and problem-based learning consistently enhance student engagement, motivation, and higher-order thinking skills. The scientific approach provides systematic learning stages, constructivism fosters independent knowledge construction, and PBL strengthens problem-solving abilities. Integrating these approaches with digital technology significantly improves the delivery and internalization of Islamic values within PAI learning. This study highlights the need for a revitalized lecture model that is adaptive, interactive, and relevant to Generation Alpha’s learning patterns. In conclusion, a technologically enriched and participatory lecture method has the potential to bridge the gap between Islamic educational traditions and the demands of digital-era learning, while making a meaningful contribution to the development of contemporary PAI pedagogy.